Theoretical study on the structural, mechanical, electronic properties and QTAIM of CrB4 as a hard material - 李小红 崔红玲 张瑞州 (中国物理B：英文版, 2017)
Using the first-principles calculations based on spin density functional theory（DFT）, we investigate the structure,elastic properties, and electronic structure of Pnnm-CrB4. It is found that Pnnm-CrB4 is thermodynamically and mechanically stable. The calculated elastic properties such as the bulk modulus, shear modulus, Young＇s modulus, and Poisson＇s ratio indicate that CrB4 is an incompressible material. Vicker＇s hardness of Pnnm-CrB4 is estimated to be 26.3 GPa, which is in good agreement with the experimental values. The analysis of the investigated electronic properties shows that PnnmCrB4 has the metallic character and there exist strong B–B and Cr–B bonds in the compound, which are further confirmed by Bader＇s quantum theory of atoms in molecules（QTAIM）. Thermodynamic properties are also investigated.